1997
DOI: 10.1016/s0009-9236(97)90148-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omeprazole pretreatment on acetaminophen metabolism in rapid and slow metabolizers of S-mephenytoin*

Abstract: Omeprazole, a widely used and potent gastric proton pump inhibitor, induces cytochrome P450 (CYP) 1A2 in humans. Induction is most pronounced in slow metabolizers of S-mephenytoin because CYP2C19 (S-mephenytoin hydroxylase) is responsible for the elimination of omeprazole. Acetaminophen (INN, paracetamol), a widely used and effective analgesic and antipyretic agent, causes serious hepatic and renal toxicity at high doses by conversion of acetaminophen to the toxic intermediate N-acetyl-p-benzoquinone imine (NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…2,3) It has been generally accepted that the role of CYP1A2 and 3A4 in generation of NAPQI is very small compared with that of CYP2E1. 3,33,34) In this study a dose of DMSO to mice decreased the microsomal CYP1A2 and 3A activities determined with aminopyrine and erythromycin as substrates. The contribution of inhibition of CYP1A2 and/or 3A activities by DMSO to the reduction of generation of a reactive metabolite from APAP in vivo is not known.…”
Section: Effect Of Dmso On Apap-induced Toxicity In Micementioning
confidence: 55%
“…2,3) It has been generally accepted that the role of CYP1A2 and 3A4 in generation of NAPQI is very small compared with that of CYP2E1. 3,33,34) In this study a dose of DMSO to mice decreased the microsomal CYP1A2 and 3A activities determined with aminopyrine and erythromycin as substrates. The contribution of inhibition of CYP1A2 and/or 3A activities by DMSO to the reduction of generation of a reactive metabolite from APAP in vivo is not known.…”
Section: Effect Of Dmso On Apap-induced Toxicity In Micementioning
confidence: 55%
“…Consistent with the findings in mice, induction of human CYP1A2 seems to have little effect on the formation of the reactive metabolite NAPQI of acetaminophen. In a clinical study with EMs and PMs of CYP2C19, omeprazole was administered orally at 40 mg daily for 7 days (226). A significant CYP1A2 induction was observed only in the PMs, but not in EMs of CYP2C19.…”
Section: Induction In Toxicitymentioning
confidence: 99%
“…Recent pharmacokinetic studies in human volunteers have demonstrated that the involvement of CYP1A2 and CYP3A4 in NAPQI formation in vivo is much less than that of CYP2E1 (Sarich et al, 1997;Manyike et al, 2000). Additionally, studies using CYP2E1 and CYP1A2 knockout mice have shown that the former, but not the latter, are more resistant to APAP-induced hepatotoxicity than are wild-type animals (Lee et al, 1996;Tonge et al, 1998;Zaher et al, 1998), indicating that among the CYPs CYP2E1 is a primary contributor to APAP biotransformation.…”
Section: Effect Of Gga On Cyp2e1 Activity and Hepatic Gsh Depletionmentioning
confidence: 99%